Cognitive Bias Affecting Decision-Making in the Legal Process - Adebola Olaborede; Lirieka Meintjes-van der Walt (Obiter, 2021)
Several empirical research studies have shown that cognitive bias can unconsciously distort inferences and interpretations made by judges either at the hearing, ruling or sentencing stage of a court trial and this may result in miscarriages of justice. This article examines how cognitive heuristics affects judicial decision-making with seven common manifestations of heuristics such as availability heuristics, confirmation bias, egocentric bias, anchoring, hindsight bias, framing and representativeness. This article contends that the different manifestations of heuristics pose a potentially serious risk to the quality and objectivity of any criminal case, despite the professional legal training and experience of judges and magistrates. Therefore, suggestions on how best to avoid and minimise the effects of cognitive heuristics, especially within South African courts are proffered. These include creating awareness raising, cross-examination and replacement.